Application of Compressive Sensing in Solving Monostatic Scattering Problems. (17th January 2019) - Chai, Shui-Rong; Guo, Li-Xin; Li, Long
Abstract : In this paper, a new CS-FMM method that conjugates compressive sensing (CS) with the fast multipole method (FMM) is proposed and validated to efficiently solve monostatic scattering from an arbitrary conducting target. The far zone scattered fields are viewed as the signal of interest. CS is introduced to reduce the number of computations. A new set of incident sources has been generated according to CS. By solving the matrix equations under the new set of incident sources and calculating the related far zone scattered fields, the measurements of the aforementioned signal can be derived. Then, the CS inversion is employed to reconstruct the desired monostatic far zone scattered fields by finding the smallest possibleℓ 1 norm solution. Monostatic radar cross section (RCS) from several conducting targets is studied by CS-FMM and by the traditional FMM. And the results are compared with each other to illustrate the accuracy and efficiency of the proposed method.